ANALISIS KEPUTUSAN INVESTASI PROYEK LPG TRANSSHIPMENT - Mufidah, Vernida
LPG demand for East Indonesia increases year by year, currently the demands are being supplied by Ship to Ship (STS) in Kalbut, East Java that cause high cost due to far distance between terminal and destination point in East Kalimantan and Sulawesi. In addition, in STS there is no blending facilities, therefore blending process in their destination. PT Badak NGL or Badak LNG which is located in East Kalimantan has LPG storage facility and jetty that can be utilized to be LPG hub to cover the demand in East Indonesia. This project will build an LPG Hub Terminal in East Kalimantan with business scheme Build, Operate and Own (BOO) and project lifetime 10 years. The project cost is divided into Capital Expenditures and Operating Expenditure. The total cost for Capital Expenditure is 295 Billion Rupiah. Meanwhile the OPEX will be divided into fixed cost and variable cost. This variable cost depend on the volume of LPG that will be processed.